Penyuluhan Pencegahan dan Penanganan Penyakit Melalui Saluran Pembuangan Air Limbah (SPAL) di Desa Datahu, Kecamatan Anggrek, Kabupaten Gorontalo Utara - Hendrik David Julianus Borolla; Juliana Juliana (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
Health is one of the needs and foundations for humans to be able to live normally by working, creating and enjoying life to the fullest in the world. One of the health problems is the cleanliness of the wastewater drainage system (SPAL). Counseling was carried out in Datahu village, Kec. Orchid, Kab. North Gorontalo, the target of extension is the community in Datahu village. The factor that is the main obstacle in the nutritional health problem of mothers and children is related to the lack of awareness of having waste water drainage channels and rubbish dumps by the Datahu village community. The aim of this outreach is to inform the community about the importance of paying attention to the nutritional conditions of mothers and children as well as handling and preventing the main problems in Datahu village. The results of the outreach were that the people of Datahu village knew how to make waste water drainage channels and the importance of having a waste disposal site to avoid nutritional problems for mothers and children in Datahu village.